The Influence of Life Skills-Based Information Services on Student Career Planning Improvement - Indiati Indiati; Hijrah Eko Putro (STKIP Singkawang, 2023)
This research was conducted to determine the effectiveness of career information using life skills techniques to improve career planning for Al-Iman High School students, in Magelang City. The research method was experimental research. The research design used a pre-experimental: one group pretest-posttest design. The research sample was class III students using non-random sampling with a quota sampling technique, amounting to 15 students. The students' career planning characteristics were measured using a career planning questionnaire. The data analysis technique used was the Paired sample t-Test with the consideration that this study used one independent variable. The results showed that this model was effective in improving student career planning. The level of student career planning increased after following career information using life skills techniques. This could be seen from the career planning of students before and after being given career information with the Life Skills technique of 22% and strengthened through an effectiveness test using a t-test which showed -t count (-7.869) < -t table (-2.120).